Konstruksi Makna Fasād dan Ihlāk dalam Perspektif Tafsir Maqāṣidī dan Relevansinya terhadap Praktik Ekosida Lahan Pascatambang - Irfan Fauzi; Imamul Burhan; Ahmad Mahrus Mariadi; Nur Arfiyah Febriani (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This article examines the socio-ecological ramifications of the post-mining land crisis in Indonesia, which necessitates a more sophisticated theological response beyond general readings of environmental degradation. This research aims to address this crisis by proposing a novel interpretation of the terms fasād (corruption/damage) and ihlāk (annihilation/destruction) in QS. Al-Baqarah: 205, utilizing a Maqashidi Tafsir approach. Methodologically, this study is a qualitative library-based research that operationalizes the Maqashidi Tafsir framework proposed by Abdul Mustaqim. The analysis is conducted through three stages: first, examining the linguistic structure and comparative meanings of fasād and ihlāk; second, extracting the maqāṣid al-sharī‘ah (objectives of Islamic law) from QS. Al-Baqarah: 205; and third, contextualizing these maqāṣidi values to evaluate the status of ecocide in Indonesia's post-mining land crisis. The results demonstrate that the term ihlāk offers a more precise conceptualization of the total destruction of ecosystems (al-ḥarṡ wa an-nasl). This practice is identified as a multidimensional violation of the maqāṣid al-sharī‘ah, namely the preservation of life (ḥifẓ al-nafs), property (ḥifẓ al-māl), and the environment (ḥifẓ al-bī’ah). Furthermore, through a protective approach, the study highlights the necessity for governmental mining control through legal policies and corporate accountability. Meanwhile, a productive approach yields progressive actions in the form of innovative post-mining recovery and sustainable development.